ANALISIS TITIK PULANG POKOK USAHA BAWANG GORENG PADA C.V DUTA AGROLESTARI DI KOTAPALU - Suhartawan, I Gede; Antara, Made; Alam, Max Nur (AGROTEKBIS, 2013)
Palu fried onion is one of the leading commodity in Palu. Unlike the other onions from Java,fried onions from Palu, Sigi, and even Donggala have a unique taste and aroma. This study aims to determine the physical production, the cost of production, selling price and the amount of revenue that the CV Duta Agrolestarireceived on fried onions in thebusiness. Therefore the business achieve break-even point. The results indicate that on average the business produce about 2600 kg fried onions per month. CV Agro Lestari must pay the total cost of production without packaging of Rp . 283.655.960. With the price of Rp.160.000/kg, obtained revenue about Rp.416.000.000, so the average income earned about Rp.132.344.040. The results of the analysis showed that the fried onions business of CV. Duta Agrolestari will achieve the break-even point if the revenue reached Rp.30.720.000/bulan or on average production reached as much as 192 kg per month, with a selling price of Rp.160.000/kg .